English Teachers' Perceptions of Their Professional Development: A Mixed-Methods Study - Xuan Jiang; Feng Li; Changmi Wang (Cranmore Publishing, 2021)
The authors applied Bruner's tenets of learning and Knowles's Adult Learning Theory to investigate Chinese English Language Teaching (ELT) teachers' perceptions of their in-service Professional Development (PD). In this mixed-methods study, 60 participants were recruited from six secondary schools in China to complete a survey. Quantitative results from the survey indicated that the respondents perceived no significant difference between the influence of overseas PD and that of domestic PD on teachers' English teaching competence and on their students' English learning outcomes. Qualitative findings highlighted that the participants expected future ELT PD to be practical, discipline-specific, language skills focused, innovative, and virtual-delivery-friendly. It should be noted that expectations of PD to be discipline-specific and virtual-delivery-friendly are new to the existing literature, which deserve more attention and further investigation.